RELATION OF INSTITUTIONAL REPUTATION COMPONENTS TO BRAND LOYALTY: A FIELD STUDY FOR GSM OPERATOR USERS - Selma KARABAŞ (Fırat University, 2019)
Institutions exist and differentiate with the various values in addition to financial resources. The long-term value of the institution must be managed by intellectual capital and the use of information technology and equipment. In this process, how consumers and all stakeholders perceive the institution is important to protect the reputation of the institution. The purpose of this study is to analyze the factors in which components of corporate reputation are represented and the relationship between components of corporate reputation with brand loyalty. For this purpose, the data obtained by the survey method were used in the study from GSM operator users via 250 people over 18 who living in Çankırı province. The data obtained from easy sampling method were subjected to “factor analysis” and “correlation analysis”. According to the results of factor analysis, it has been determined that corporate reputation can be explained by four factors (emotional trust, performance and leadership, customer value and sense of responsibility). In order to measure the relationship between corporate reputation and brand loyalty according to the results of performed correlation analysis; there is a positive and meaningful relationship between corporate reputation and brand loyalty.